Analysis of the population genetic structure and demographic history of Tilia amurensis and Tilia japonica in China using SSR markers - Zhang, Yue; Zang, Fengqi; Liu, Dan; Ma, Yan; Lu, Yizeng; Wu, Qichao; Zang, Dekui (Frontiers in Plant Science, 2025)
Tilia amurensis, a deciduous broad-leaved tree, is distributed in regions neighboring those of Tilia japonica populations in China; these plants belong to the Malvaceae family. To date, the genetic status and demographic history of T. japonica remain unknown, and the demographic history of T. amurensis is not well defined. This study uses standard population genetic and approximate Bayesian computation (ABC) analyses of SSR data to determine the genetic status and divergence times of these two lime taxa. The results revealed that the genetic diversity of T. japonica (I = 1.181, HO = 0.484, HE = 0.602) was high at the population level. The results of the genetic structure revealed that the genetic variation was dominated primarily by within-population variation. Additionally, there was significant genetic differentiation and bidirectional introgression between T. amurensis and T. japonica. The ABC analysis suggests a (Middle) Pleistocene divergence. These findings have important implications for the formulation of appropriate conservation strategies. Specifically, the clarified divergence time and evidence of genetic exchange indicate that the two species should be protected based on their respective population conditions.